Central Lung Cancer Management: Impact of Bronchial Resection Margin Length - Kim, Dohun; Kim, Hong Kwan; Choi, Yong Soo; Kim, Kwhanmien; Kim, Jhingook; Shim, Young Mog (The Thoracic and Cardiovascular Surgeon, 2015)
Purpose The purpose of this study was to analyze the clinical impact of bronchial resection margin length in centrally located, non-small cell lung cancer.Materials and Methods A total of 1,854 pulmonary resections were performed between January 1994 and December 2005. Central lung cancer was defined as a tumor that was confirmed by bronchoscopy or a malignancy proven by bronchoscopic washing. Cases with neoadjuvant treatment that could alter the malignancy on the margin and those without documentation of margin length were excluded. To divide the study group into two groups, the cutoff value for the margin length was calculated by the minimum p-value approach. Clinical variables were then compared between the two groups and prognostic factors for survival were analyzed.Results A total of 573 patients were included. The patients were divided into two groups based on margin length, short (< 19 mm) and long (≥ 19 mm). Overall survival and disease-free survival were superior in the short length group by univariate analysis (p = 0.03, 0.02). With multivariate analysis, advanced age (p < 0.00, 0.00), pneumonectomy (p < 0.00, 0.00), advanced pathologic stage (p < 0.00, 0.00), and no adjuvant chemotherapy (p < 0.00, 0.01) were poor prognostic factors for survival; however, bronchial resection margin length was not a statistically significant factor (p = 0.90, 0.96).Conclusion A long bronchial resection margin length may not guarantee better oncologic outcomes in central lung cancer patients. Rather, avoiding pneumonectomy and the application of adjuvant chemotherapy should be considered to survival.
Keywords: lung cancer treatment; surgery; outcomes